An Interprofessional Interpretation of Ontario’s CPSO End-of-Life Policy - Sklar, Michael; Walker, Quinn; Lewis, Ellen; Born, Karen; Sas, Courtney (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
In the acute care setting, we often ask families to make challenging decisions regarding their loved ones’ preferences and choices for end-of-life care when these individuals can no longer make those decisions themselves. This already stressful situation can be exacerbated by medical jargon and conflicting messaging from various well-meaning health care practitioners. Some of this ambiguity likely stems from medical providers’ lack of familiarity with end-of-life policies and their obligations as providers. Further, there can be discomfort for many families and clinicians about speaking about end of life, alongside varying cultural norms and expectations around death and dying. In this analysis, we aim to outline fundamental concepts and misconceptions surrounding cardiopulmonary resuscitation, the administration and withdrawal of life-sustaining therapies, and the framework provided by regulatory bodies for medical professionals to approach these situations. As legal and ethical principles may vary nationally between jurisdictions, our discussion will be based on Ontario policy and law. However, we believe that a similar approach would help hospitals and health care bodies provide clarity to clinicians, patients and families alike, and could be easily adapted into medical education materials.